1998
DOI: 10.1524/ract.1998.82.special-issue.293
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Solution Distribution Coefficients, Kd s, of I- and IO- 3 for 68 Japanese Soils

Abstract: Soil-solution distribution coefficients, K d s, of I and IO s were measured by a batch method using 125 I for 68 wet (fresh) and autoclaved soils collected from upland fields, paddies, forests and open areas throughout Japan. Nine soil properties, such as soil-pH, cation exchange capacity (CEC), anion exchange capacity (AEC), active-Al (extractable Al by oxalic acid + ammonium oxalate) and total organic carbon (TOC), were also measured. The K d s for wet soils ranged widely from 1.1 to 10,200 1 kg"' for I" and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 12 publications
3
27
0
1
Order By: Relevance
“…In lysimeter studies of four soils with organic contents ranging from 0.2-6.8 wt %, Sheppard and Thibault (1991) measured K d values that were 1-2 orders of magnitude higher in the organic-rich soils relative to the organic-poor soils. Similar results were shown in comparative studies by Yoshida et al (1992), Bird and Schwartz (1996), Sheppard et al (1996), and Yoshida et al (1998). Kaplan (2003) compared iodide uptake by two sediments that had similar grainsize, mineralogy, and pH values, but had very different organic carbon contents, <0.02 versus 0.14 wt %.…”
Section: Influence Of Sediment Organic Matter On Iodine Sorptionsupporting
confidence: 80%
See 1 more Smart Citation
“…In lysimeter studies of four soils with organic contents ranging from 0.2-6.8 wt %, Sheppard and Thibault (1991) measured K d values that were 1-2 orders of magnitude higher in the organic-rich soils relative to the organic-poor soils. Similar results were shown in comparative studies by Yoshida et al (1992), Bird and Schwartz (1996), Sheppard et al (1996), and Yoshida et al (1998). Kaplan (2003) compared iodide uptake by two sediments that had similar grainsize, mineralogy, and pH values, but had very different organic carbon contents, <0.02 versus 0.14 wt %.…”
Section: Influence Of Sediment Organic Matter On Iodine Sorptionsupporting
confidence: 80%
“…Many researchers have tested this hypothesis by comparing iodine sorption onto sterilized and unsterilized soils (Behrens, 1982;Bird and Schwartz, 1997;Sheppard, 1995;Yoshida et al, 1998). These studies have confirmed that microbial activity is involved, but the nature of that involvement is unresolved.…”
Section: Radioiodine Sorption Studies At Hanfordmentioning
confidence: 99%
“…Une partie de ces dernières valeurs, sources des données par défaut, doit être négligée, en raison de conditions de détermination trop particulières. Par exemple, certains Kd ont été acquis sur du charbon de bois, considéré ensuite comme sol de catégorie « organic » ou bien sur des substrats du sous-sol ; de même, les valeurs très élevées obtenues par Yoshida et al (1998) sur des andosols sont écartées en raison du caractère spécifique de ces sols que l'on n'observe que rarement (Puy de Dôme) en France. Si l'on excepte ces valeurs très élevées, le pool de données de l'intervalle 0-100 L kg -1 présente une moyenne géométrique de 3 pour un intervalle de valeurs variant de 0,04 à 120.…”
Section: Kdunclassified
“…Organic iodo compounds are not soluble and form readily through reaction with I 2 and, to a lesser extent, I - (Lieser and Peschke, 1982;Couture and Seitz, 1985); retention of iodine in soils is mostly associated with the organic matter (Wildung et al, 1974;Muramatsu, et al, 1990;Gu and Schultz, 1991;Yoshida et al, 1998;Kaplan et al, 2000). Several studies have suggested that fixation of iodine by organic soil compounds appears to be dependent upon microbiological activity, because sterilization by heating or radiation commonly results in much lower iodine retention (Bunzl and Schimmack, 1988;Koch et al, 1989;Muramatsu et al, 1990;Bors et al, 1991;Rädlinger and Heumann, 2000).…”
Section: Imentioning
confidence: 99%